UTHM TRADEHUB: Pusat Teknousahawan Universiti - ARIFF HAFIZAL BIN AHMAD HUSNI; Mohamad Firdaus Ab Aziz (Applied Information Technology And Computer Science, 2025)
In the current digital era, accessibility, communication and efficiency Transactions are all hindered by the absence of a platform dedicated to UTHM employees and students buy, sell, bid and convert items. To solve this problem, the UTHM TradeHub system was created, offering an online e-commerce platform designed Special for the UTHM community. In order to encourage the environment more integrated and effective trade in the institution, The project is trying to develop a simple platform used and safe that facilitates the exchange of goods Using cash systems, bidding and exchanging goods. Design, the development and implementation of the e-commerce system that facilitates transactions, support various trading techniques and guarantee Consumer data security is the main goal of this research. The system uses the MySQL database along with Common web development tools include HTML, CSS, Javascript, PHP, and the style of prototype development. Functional and usable tests is part of the test steps to ensure the platform Meet the user’s needs. The results indicate that UTHM TradeHub succeeded in increasing user satisfaction, reduces reliance on third -party platforms and Make trading opportunities more accessible. Improvement user participation and preference for barter and bid systems Compared to regular cash -based transactions are three trends important it has been observed. In short, the UTHM TradeHub System offers effectively custom solutions for needs UTHM Community Trade. It encourages staff and students to trade in a more effective way and Save time. To further enhance the user experience and the platform’s negligence, future work may involve Combination of sophisticated features such as real-time notifications, Support for mobile applications and recommendation systems based on AI.